Major Determinants of Innovation Performance in the Context of Healthcare Sector - Nassani, Abdelmohsen A; Javed, Asad; Rosak-Szyrocka, Joanna; Pilar, Ladislav; Yousaf, Zahid; Haffar, Mohamed (International journal of environmental research and public health, 2023)
Through the innovation network (IN) and the use of artificial intelligence (AI), this study aims to look into the innovation performance (IP) of the healthcare industry. Digital innovation (DI) is also tested as a mediator. For the collection of data, cross-sectional methods and quantitative research designs were used. To test the study hypotheses, the SEM technique and multiple regression technique were used. Results reveal that AI and the innovation network support the attainment of innovation performance. The finding demonstrates that the relationship between INs and IP links and AI adoption and IP links is mediated through DI. The healthcare industry plays a vital role in facilitating public health and improving the living standards of the people. This sector's growth and development are largely dependent on its innovativeness. This study highlights the major determinants of IP in the healthcare industry in terms of IN and AI adoption. This study adds to the literature's knowledge via an innovative proposal in which the mediation role of DI among IN-IP and AI adoption-innovation links is investigated.
Keywords: Health Care Sector; Artificial Intelligence; Cross-Sectional Studies; Creativity; umělá inteligence; Humans; lidé; sektor zdravotní péče; průřezové studie; regresní analýza; kreativita; Regression Analysis